Relative Rate of Maternal Deaths in Pakistani Population due to sepsis - Fakharunnisa, Qamarunissa Muhabbat, Zaheer, Sajida Muneer, Waqarunnissa Ahmed, Fahmeeda Parveen (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the relative rate of maternal deaths in Pakistani population due to sepsis including the most common causative agent. Methods: The proposed study was a retrospective study model which was mainly conducted at a tertiary care hospital of Lodhran district-Punjab, Pakistan from 2019-2021 in association with the cases of maternal deaths due to sepsis reported and observed at the Gynecology & Obstetrics department of different tertiary care hospitals. Total 1200 number of participants had been examined in this study and the convenient sampling technique was used. Whereas, it discusses the maternal mortalities due to different types of sepsis during, between, and after the delivery of a baby. with diagnosed 50% cases reported for the maternal deaths due to sepsis. Data was analyzed using SPSS VR 20.0 with level of significance being kept at P-value <0.001. Results:As per the observation, out of 1200 samples, 640 samples were culture-positive, including mixed culture growth. Highest percent positivity was showed up by Streptococcus pyogenes 640(53.33%), followed by Chlamydia psittaci 80(6.66%), Mycobacterium tuberculosis 120(10%), Escherichia coli 80(6.66%), Neisseria meningitidis 40(3.33%), and Epstein-Bar virus 40(3.33%). Different approaches of delivery, gender, and respiratory infections, and the time of admission to the hospital along with the qSOFA (Quick Sequential Organ Failure Assessment) Criteria were significantly associated with sepsis. ConclusionGroup A Streptococcus (i.e.Streptococcus pyogenes strains) were the most active causative agents 640(53.33%) in inducing maternal sepsis leading to deaths. Therefore, proper preventive measures should be taken before, during and after the delivery (antepartum, post-partum) to reduce the dependent and independent risk factors and subsequently to decrease the burden of maternal deaths due to sepsis.